La Ville botanique - Maria A. Villalobos H. (Projets de Paysage)
The aim of this thesis is to elaborate and estimate a new urban model : "the botanical city". Indeed, the matter is to understand a) in which measure the urban landscape could be based on the historical model of botanical gardens b) if this apparently utopian urban model, which would be situated beyond the opposition art-science, nature-culture, can be operative. The selective analysis of botanical gardens from the 16th century to nowadays will tackle the issue of the evolution in the botanical gardens, and of their pertinence as urban models. It will determine the way the botanical gardens are put together, how the scenography is supposed to give access to the knowledge of plants and if this manner to offer to see, to understand, and to know can be transposed at the scale of a city. At the same time, the understanding of the methodological and practical conditions of this passage from the scale of a garden to the one of a city will give way to a reflection on the necessary indicators to render an account of the eventual social fallouts of this landscape operation. From then on, we shall understand those parameters on a defined ground which will have to be restored, not as a spot in the urban landscape, but as as the focal point of the urban landscape under reconstruction : the Botanical Garden of Maracaibo (1980) in Venezuela, by Roberto Burle Marx. Finally, we shall come back on the status of the notion of botanical garden. Does the botanical garden offer the basis to lay down the foundations of an new urban landscape which would promote the knowledge and sensibility of Nature and of Culture, beyond the philosophical and social oppositions ?